Trade Agreements and Enforcement : Evidence from WTO Dispute Settlement - Bown, Chad P.; Reynolds, Kara Marie (World Bank, Washington, DC, 2015)
This paper examines the implications of the terms-of-trade theory for the determinants of outcomes arising under the enforcement provisions of international agreements. Like original trade agreement negotiations, the paper models formal trade dispute negotiations as potentially addressing the terms-of-trade externality problem that governments implement import protection above the globally efficient level so as to shift some of the policys costs to trading partners. The approach is to extend earlier theoretical models of trade agreement accession negotiations to the setting of enforcement negotiations in order to guide the empirical assessment. The paper uses instrumental variables to estimate the model on trade volume outcomes from World Trade Organization (WTO) disputes over 1995–2009. The evidence is consistent with theoretical predictions that larger import volume outcomes are associated with products that have smaller increases in foreign exporter-received prices (terms-of-trade losses for the importer) as a result of the dispute, larger pre-dispute import volumes, larger import demand elasticities, and smaller foreign export supply elasticities. Dispute settlement outcome differences are also explained by variation in institutionally-motivated measures of retaliation capacity and the severity of the free-rider problem associated with foreign exporter concentration.